Thalidomide for the Treatment of Thrombocytopenia and Hypersplenism in Patients With Cirrhosis or Thalassemia - Chen, Yaocheng; Cai, Ning; Lai, Yongrong; Xu, Weiwei; Li, Jinyan; Huang, Lan; Huang, Ying; Hu, Meiling; Yang, Huangju; Chen, Jiangming (Frontiers in Pharmacology, 2020)
Hypersplenism and thrombocytopenia are common complications of liver cirrhosis or thalassemia, but current treatment strategies are limited. This study aimed to evaluate the efficacy and safety of thalidomide in the treatment of hypersplenism and thrombocytopenia in patients with liver cirrhosis or thalassemia. A total of 31 patients with hepatic cirrhosis(n=19) or thalassemia (n=12) diagnosed with hypersplenism and thrombocytopenia (platelet count [PLT] <100×109/L) were included in this prospective cohort study between January 2015 and May 2017. Patients were treated with thalidomide (150–200 mg/d) plus conventional therapy. Spleen length, PLT, leukocyte count (WBC), absolute neutrophil count (ANC) and hemoglobin level (Hb) were measured at baseline, 3 months, 6 months and 12 months. Any adverse events were noted. All of the 31 patients were showed a progressive increase PLT during the 12-month follow-up, and similar results were obtained when subgroup analyses were performed based on the primary disease (cirrhosis or thalassemia). WBC, ANC and Hb also increased progressively during the 12-month follow-up. Spleen length decreased progressively during the follow-up. No serious adverse events occurred. Thalidomide is a potential treatment for thrombocytopenia caused by hypersplenism in patients with cirrhosis or thalassemia.